Psychological wellbeing and physical activity in children and adolescents with inflammatory bowel disease compared to healthy controls - Laura Mählmann; Markus Gerber; Raoul I. Furlano; Corinne Legeret; Nadeem Kalak; Edith Holsboer-Trachsler; Serge Brand (BMC Gastroenterology, 2017)
Abstract Background Children and adolescents with inflammatory bowel disease (IBD) report impairments in daily activities, social interactions and coping. Findings regarding psychological functioning are inconsistent, while limited information is available on objectively assessed physical activity (PA). The aims of the present study were therefore to compare anthropometric dimensions, blood values, psychological functioning and PA of children and adolescents with IBD with healthy controls. Methods Forty-seven children and adolescents took part in the study. Of these, 23 were diagnosed with IBD (mean age: 13.88 years, 44% females). The IBD group was divided into a medically well adjusted “remission-group” (n = 14; IBD-RE) and a group with an “active state” of disease (n = 8; IBD-AD). Healthy controls (n = 24; HC) were age- and gender-matched. Participants’ anthropometric data, blood values and objective PA were assessed. Further, participants completed questionnaires covering socio-demographic data and psychological functioning. Results Participants with IBD-AD showed higher erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) values, haemoglobin, and leukocyte values. IBD-AD had poorer psychological functioning and lower PA (average steps per day) compared to IBD-RE and HC. No mean differences were found between IBD-RE and HC. Conclusions The pattern of results suggests that effective medical treatment of IBD in children and adolescents is associated with favorable physiological parameters, psychological dimensions and PA. Psychological counselling of children and adolescents in an active state of IBD seem to be advised in addition to standard treatment schedules. Trial registration NCT NCT02264275 ; Registered 8 October 2014.